Asperidine B: Total synthesis and structure correction. Issue 27 (2nd July 2020) - Waddell, Lachlan J.N.; Watts, Olivia F.B.; Saetang, Praphatsorn; Rukachaisirikul, Vatcharin; Bates, Roderick W.
Graphical abstract: Highlights: Synthesis of the proposed structure of Asperidine B. Use of hydroformylation and organozinc addition. Structure reassigned as (+)-preussin. Abstract: A synthesis of the proposed structure of asperidine B is reported, involving a tandem hydroformylation-condensation reaction, a diastereoselective dihydroxylation and the addition of an organozinc reagent to an iminium ion. As the spectroscopic data for the synthetic material is not in agreement with that of the natural product, the structure of asperidine B is reassigned as (+)-preussin.